Placental 11β-Hydroxysteroid dehydrogenase type 2 expression: Correlations with birth weight and placental metal concentrations. Issue 11 (November 2015) - Mikelson, C.; Kovach, M.J.; Troisi, J.; Symes, S.; Adair, D.; Miller, R.K.; Salafia, C.; Johnson, K.; Lin, Z.; Richards, S.
Abstract: Introduction: Infants born below 2500 g are classified as low birth weight. Excess in utero exposure to cortisol has been linked to restricted fetal growth. Placental production of 11β-hydroxysteroid dehydrogenase type 2 (11β-HSD2) inactivates cortisol before passage into the fetus. The present study tested the hypothesis that placental 11β-HSD2 expression is positively correlated with an individualized birth weight centile and raw birth weight, and examines the relationship between metal concentrations in placental tissue and 11β-HSD2 expression. Methods: Placentae from 191 births were collected and samples preserved to maintain mRNA profile. Placental 11β-HSD2 expression was measured via qRT-PCR. Addition samples were collected from placental tissues and uniformly dried in order to quantify 18 metals via ICP-MS (n = 160). Results: A significant, positive correlation between 11β-HSD2 expression and individualized birth weight centile (p = 0.0321) and birth weight (p = 0.0243) was found. Additionally, maternal age and gestational age were positivity correlated with each other (p = 0.0321). Birth weight was significantly different with race, marital status, education and maternal tobacco use. Four metals (Co, Mn, Ni, Zn) demonstrated significant positive correlations (p < 0.05) with 11β-HSD2 expression. Sex specific differences were found; Co, Cu, Fe, Zn, and Ni were positively correlated with 11β-HSD2 expression in males only, no significant correlations were found in the female only sample. Conclusion: These data indicate that the growth potential of a fetus is related to the 11β-HSD2 expression in the placenta, and that 11β-HSD2 expression is related to the trace metals status of the mother. Highlights: A significant positive correlation was seen with 11β-HSD2 expression and birth weight. A significant positive correlation was seen with expression and birth weight centile and birth weight. 11β-HSD2 expression is positively correlated with Co, Mn, Ni and Zn within all births. Expression and Co, Ni, Zn, Fe and Cu are positively correlated within male births. Female births did not show any correlations between expression and metal abundance.